Improving Nangsri Bell Tourism through Social Media And Photobooth Creating - Iswanto Suwarno; Robbi Rahim; Mohammad Aljanabi; Omar Tanane; Erwin L. Rimban; Toha Ardi Nugraha (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
There is a tour that forms the border between the Nangsri Kidul and Nangsri Lor combinations, namely the Nangsri Lake tour. Nangsri Lake is one of the tours located on the border of the Nangsri Kidul and Nangsri Lor Villages, Candirejo Village, Kapanewon Semanu, Gunung Kidul Regency. Nangsri Lake is surrounded by large shady trees so the atmosphere is very cool and beautiful. The view at Nangsri Lake is also soothing to the eye. But unfortunately not many Yogyakarta residents know about the existence of Telaga Nangsri. Due to the corona pandemic that hit Indonesia in the Yogyakarta area, Nangsri Lake is increasingly empty of visitors. This is what underlies the KKN group and UMY Community Service Time to introduce Telaga Nangsri tourism to the people of Yogyakarta and outside Yogyakarta. To introduce and enliven Nangsri Lake tourism, our group made several work programs. The first work program is to create content for the tourism promotion of Nangsri Lake. The second work program is to make a photobooth that can be used as a photo facility at Nangsri Lake. The activity program can increase visitors to Nangsri Lake.